International pediatric liver cancer pathological classification: current trend - Tanaka, Yukichi; Inoue, Takeshi; Horie, Hiroshi (International Journal of Clinical Oncology, 2013)
This review describes the pathological classification of pediatric liver cancer types and subtypes proposed at the recent international symposium (March 2011, Los Angeles, USA) and meetings involving pathologists serving as central reviewers for the Children’s Oncology Group, Société Internationale d’Oncologie Pédiatrique, Gesellschaft für Pädiatrische Onkologie und Hämatologie, or Japanese Study Group for Pediatric Liver Tumors, and pediatric oncologists/surgeons specializing in liver cancers, as well as immunohistochemical panels, recommendations for submission, sampling and evaluation of diagnostic specimens. The pathological classification is intended to be standardized and clinically meaningful, thus improving future patient management and prognosis. The most common pediatric liver cancer is hepatoblastoma (HBL). HBL has two types, the wholly epithelial type and the mixed epithelial and mesenchymal (MEM) type. The wholly epithelial type was subdivided into well-differentiated fetal (pure fetal with low mitotic activity), crowded fetal (mitotically active), embryonal, epithelial mixed, small cell undifferentiated, and cholangioblastic. A macrotrabecular pattern and a pleomorphic epithelial pattern were recognized as supplemental features of epithelial components. The MEM type was subdivided into MEM without teratoid features and MEM with teratoid features. Other liver cancers in children were divided into hepatocellular carcinoma (classic hepatocellular carcinoma and fibrolamellar carcinoma) and hepatocellular malignant tumor not otherwise specified. This classification is basically applied to pretreatment specimens; the evaluation of post-chemotherapy specimens will be the subject of further studies.